2020
DOI: 10.33369/jvk.v3i2.12884
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Hypercolesterolemia in Lansia in the Working Area of Puskesmas Daik 2020

Abstract: Hypercholesterolemia is one of the causes of metabolic disorders that cause coronary heart disease, blood vessels and diseases related to blockage of blood vessels. WHO data in 2015 states that more than 17 million people worldwide die from coronary heart disease and blood vessels. The results of screening for the elderly in the Daik Community Health Center Work Area in 2019, of the 398 elderly who were examined, there were 283 elderly who had hypercholesterolemia, namely 71.1% of the elderly with cholesterol&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A quantitative statistical study by Rubiah et al in 2020 on 165 elderly patients (aged 65 -75 years) that were confirmed to have high serum cholesterol at a Health Center in Daik, Riau Islands Province, found that the habit of eating food containing high-fat and less physical exercise had a significant influence on the occurrence of hypercholesterolemia (6) . A study by Widiyono et al in 2021 at an Integrated Health Service Post (Posyandu) in the village of Betengsari Kartasura on 29 elderly patients that had been confirmed to have hypercholesterolemia found that 89.7% had a history of frequently consuming food rich-in fat, 100% not doing regular exercise, and 10.3% having a habit of cigarette smoking (7) .…”
Section: Discussionmentioning
confidence: 99%
“…A quantitative statistical study by Rubiah et al in 2020 on 165 elderly patients (aged 65 -75 years) that were confirmed to have high serum cholesterol at a Health Center in Daik, Riau Islands Province, found that the habit of eating food containing high-fat and less physical exercise had a significant influence on the occurrence of hypercholesterolemia (6) . A study by Widiyono et al in 2021 at an Integrated Health Service Post (Posyandu) in the village of Betengsari Kartasura on 29 elderly patients that had been confirmed to have hypercholesterolemia found that 89.7% had a history of frequently consuming food rich-in fat, 100% not doing regular exercise, and 10.3% having a habit of cigarette smoking (7) .…”
Section: Discussionmentioning
confidence: 99%